Pengaruh Kemampuan Numerik dan Cara Belajar terhadap Prestasi Belajar Matematika - Farah Indrawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
The goal of this research are for knowing the together effect of the numeric ability and the study method to the result of mathematic study, the effect of the numeric ability to the result of mathematic study and the effect of the study method to the result of mathematic study (survey at SMAI Al-Azhar, South of Jakarta). The population is the tenth class (Senior High School) which is ammount 191 students and chosen 96 students as sample by random method. The collection of data takes by writing test of the numeric ability, scatter questions of the study method and collects data the rapor value of mathematic study in odd semester. The test of data process by using regression of SPSS-20 computer programme. The result from this research gets the linier regression Y = 77,047 – 0,009 X1 – 0,101 X2, it means no together significant effect between the numeric ability and the method study to the result of mathematic study. The numeric ability and the study method no properly to use for predicting the result of mathematic study.